Solving Integral Equations by Common Fixed Point Theorems on Complex Partial b-Metric Spaces - Arul Joseph Gnanaprakasam; Salah Mahmoud Boulaaras; Gunaseelan Mani; Mohamed Abdalla; Asma Alharbi (Journal of Function Spaces)
In this paper, we prove some common fixed point theorems for rational contraction mapping on complex partial b-metric space. The presented results generalize and expand some of the literature’s well-known results. We also explore some of the applications of our key results.